Detrital zircon U–Pb LA‐ICPMS ages from the Kolhan Group, Singhbhum Craton, eastern India: Implications for terminal Mesoproterozoic palaeogeography between Columbia and Rodinia along the Central Indian Tectonic Zone. (12th August 2020) - Mukhopadhyay, Joydip; Crowley, Quentin; Ghosh, Bhaskar; Ghosh, Gautam; Heron, Kyle
Abstract : The Kolhan Group in the Singhbhum Craton of eastern India is a passive margin siliciclastic shelf to deep‐water carbonate ramp platform succession. It occupies a unique position in respect of the Central Indian Tectonic Zone (CITZ), widely considered as the suture joining the northern and southern Indian cratonic blocks at the time of amalgamation of the Mesoproterozoic supercontinent Columbia. The Kolhan succession is closely comparable to other Late Proterozoic 'Purana' successions of India including the siliciclastic‐carbonate Suasar Group from the central part of the CITZ. We report here the first U–Pb detrital zircon ages from the Kolhan Group. The youngest age population obtained from basal siliciclastics suggests it is not older than ca. 1, 158 Ma. The absence of any concordant detrital zircon <1, 000 Ma which is well represented in the adjoining Singhbhum Shear Zone and CITZ extensions, suggests that the sedimentation took place prior to ca. 1, 000 Ma. The Kolhan Group, therefore, records an extensional event between two major episodes of supercontinent assembly (i.e., Columbia and Rodinia). A similar motif of extension and passive margin sedimentation across Mesoproterozoic Peninsular India together with the widespread Mesoproterozoic lamproite and kimberlite emplacement event suggests an episode of extension and major basin development across the Indian Shield in between the two supercontinent amalgamation cycles of Columbia and Rodinia. Abstract :